Dynamics of the Physicochemical Characteristics, Microbiota, and Metabolic Functions of Soybean Meal and Corn Mixed Substrates during Two-Stage Solid-State Fermentation - Cheng Wang; Changyou Shi; Weifa Su; Mingliang Jin; Bocheng Xu; Lihong Hao; Yu Zhang; Zeqing Lu; Fengqin Wang; Yizhen Wang; Huahua Du (mSystems, 2020)
ABSTRACT Substantial annual economic loss in livestock production is caused by antinutritional factors in soybean meal and corn mixed substrates, which can be degraded by microbial fermentation. Although considerable efforts have been made to explain the effects of fermentation on soybean meal and corn-based feed, the dynamics of the physicochemical characteristics, microbiota, and metabolic functions of soybean meal and corn mixed substrates during solid-state fermentation remain unclear. Here, multiple physicochemical analyses combined with high-throughput sequencing were performed to reveal the dynamic changes that occur during a novel two-stage solid-state fermentation process. Generally, inoculated bacteria rapidly proliferated in the initial 12-h aerobic fermentation (P = 0.002). Notably, most nutritional changes occurred during 12 to 24 h compared to 0 to 12 h. Second-stage anaerobic fermentation increased the bacterial abundance and lactic acid content (P < 0.00). Bacillus spp., Enterococcus spp., and Pseudomonas spp. were predominantly involved in the maturation of the fermented mixed substrates (P < 0.05). Additionally, the available phosphorus exhibited the greatest interaction with the microbial community structure. Cellular processes and environmental information processing might be the main metabolic processes of the microbiota during this fermentation. An in vivo model further evaluated the growth-promoting effects of the fermented products. These results characterized the dynamic changes that occur during two-stage solid-state fermentation and provided potential references for additional interventions to further improve the effectiveness and efficiency of solid-state fermentation of feed. IMPORTANCE Solid-state fermentation (SSF) plays pivotal roles not only in human food but also farm animal diets. Soybean meal (SBM) and corn account for approximately 70% of the global feed consumption. However, the nutritional value of conventional SBM and corn mixed substrates (MS) is limited by antinutritional factors, causing substantial economic loss in livestock production. Although emerging studies have reported that SSF can improve the nutritional value of SBM-based substrates, the dynamic changes in the physicochemical features, microbiota, and metabolic functions of MS during SSF remain poorly understood, limiting further investigation. To provide insights into the dynamics of the physicochemical characteristics and the complex microbiome during the two-stage SSF of MS, multiple physicochemical analyses combined with high-throughput sequencing were applied here. These novel insights shed light on the complex changes that occur in the nutrition and microbiome during two-stage SSF of MS and are of great value for industrial feed-based practices and metabolomic research on SSF ecosystems.